Critical notes on the unpublished appendix «Encuentros con César Vallejo» by Leopoldo de Luis (Castilla. Estudios de Literatura, 2023)
This contribution presents an analysis of the recovered unpublished text "Encuentros con César Vallejo" by the poet and critic Leopoldo de Luis. De Luis's comments offer a synthesis that can be considered essential in the Hispanic poetics that has emerged in contemporary times and of which Vallejo is a main part. The interpretation of de Luis, integrating critical historicism and its traditions to the commentary in the text, is exemplary and hence its publication, since it unites two moments by linking criticism of Vallejo with the very coordinates of poetics in the context lived by Leopoldo de Luis.
Keywords: César Vallejo; Leopoldo de Luis; criticism; hispanism